Sally Dows - Harte, Bret, 1836-1902 (Salt Lake City, UT : Project Gutenberg, 2006)
"Sally Dows" by Bret Harte is a novel likely written in the late 19th century. The story appears to focus on the life of Sally Dows, a Southern woman navigating the complexities and aftermath of the Civil War, particularly in relation to her relationships with men who have fallen for her, which is highlighted by the opening chapter's engagement with themes of valor and loss in wartime. The opening of the novel presents a vivid prologue that paints a scene of desolation following a battle, where remnants of soldiers and equipment lie scattered. The narrative follows a young artillery officer who discovers the photograph and letter of a deceased soldier addressed to Sally Dows, sensing a deeper connection to her as a once-enigmatic figure. Following the prologue, the story shifts to a train journey to Redlands, Georgia, where two passengers, Colonel Courtland and Mr. Drummond, discuss the state of the South after the war. Here, Courtland's thoughts turn toward Sally Dows, who seems to embody hope amidst the ruin, drawing on her determination to rebuild and modernize her family$1 (Bs estate after the devastation of war. As the young men arrive at Dows' Folly, we see the beginnings of personal entanglements with Sally that set the stage for the evolving dynamics of relationships in a post-war society. (This is an automatically generated summary.)s
Sally Dows -- The conspiracy of Mrs. Bunker -- The transformation of Buckeye camp -- Their uncle from California.
Release date is 2006-05-25
Produced by Donald Lainson; David Widger
Keywords: Western stories; American fiction -- 19th century